Thermal stability of V–W–Cr–Zr alloy after high-pressure torsion - Smirnov, I. V.; Ditenberg, I. A.; Tolstikhin, V. I. (Russian physics journal, 2025)
Complex studying of thermal stability of the V–W–Cr–Zr alloy is studied after plastic deformation under torsion at high pressure. Methods of scanning and transmission electronic microscopy are used to study the influence of the temperature on the characteristics of grain, defective, and heterophase structures. A comparison of the results of structural attribution with microhardness values has allowed the main temperature intervals of realization of relaxation processes to be elucidated. It has been established that under the influence of the temperature, the processes of heterophase structure transformations are the main factors determining the thermal stability of the V–W–Cr–Zr alloy. The presence of finely dispersed particles of the second phases promotes preservation of an anisotropic submicrocrystalline state and high microhardness values up to 700 °C. Beginning at 800 °C, the coagulation of particles leads to partial unblocking of dislocation substructures accompanied by the return processes and primary recrystallization gradually encompassing the entire volume of the material. Secondary recrystallization comes to the end at 1100 °C. The relaxation processes in the temperature interval from 800 to 1100 °C are accompanied by the reduction of microhardness values, the character of change of which is determined by the Hall–Petch relation taking into account the joint disperse and grain-boundary hardening.